2019
DOI: 10.1007/s00253-019-10010-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics and functional analysis of a highly adhesive dairy Lactobacillus paracasei subsp. paracasei IBB3423 strain

Abstract: Various Lactobacillus paracasei strains are found in diverse environments, including dairy and plant materials and the intestinal tract of humans and animals, and are also used in the food industry or as probiotics. In this study, we have isolated a new strain L. paracasei subsp. paracasei IBB3423 from samples of raw cow milk collected in a citizen science project. IBB3423 showed some desired probiotic features such as high adhesion capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 92 publications
1
13
0
Order By: Relevance
“…3a). These data underlined the high number of proteins related to carbohydrate and amino acid transport and metabolism, in accordance with the wide range of sugars metabolized by members of this species (31,62) and with the apparent inability of lactobacilli to synthetize most amino acids (63). Recently, an orthologue of the Escherichia coli glgX gene, which is involved in glycogen metabolism, was identified in L. crispatus genomes (54).…”
Section: Fig 1 Legend (Continued)supporting
confidence: 53%
“…3a). These data underlined the high number of proteins related to carbohydrate and amino acid transport and metabolism, in accordance with the wide range of sugars metabolized by members of this species (31,62) and with the apparent inability of lactobacilli to synthetize most amino acids (63). Recently, an orthologue of the Escherichia coli glgX gene, which is involved in glycogen metabolism, was identified in L. crispatus genomes (54).…”
Section: Fig 1 Legend (Continued)supporting
confidence: 53%
“…A previous study has shown that Bacillus subtilis and Bacillus Coagulans could improve abdominal pain and diarrhea in irritable bowel syndrome (IBS) patients ( Rogha et al, 2014 ). Lactobacillus equigenerosi and Lactobacillus paracasei belonging to the genus Lactobacillus could activate macrophages to suppress inflammation in IBS patients ( Koryszewska-Baginska et al, 2019 ). Lactococcus lactis ssp.…”
Section: Discussionmentioning
confidence: 99%
“…We further identified this isolate as a novel strain L. paracasei LP10266 based on Vitek MS, 16S rRNA polymerase chain reaction (PCR), and biochemical tests. High-throughput sequencing technology [ 16 ] was used to predict the tissue invasion and identify biomarkers implicated in the pathogenicity of lactobacilli [ 17 ]. Our results have demonstrated that L. paracasei LP10266 has shown shared pathogenic properties with other pathogenic bacteria and evolved multiple mechanisms to adapt and survive in human body.…”
Section: Introductionmentioning
confidence: 99%